Peningkatan Kesadaran Menabung Bagi Kaum Muda Melalui Sosialisasi The Importance of Saving - Junianta, Maria; Elvi, Fitria; Masiun, Stefanus; Bertus, Adil; Sara, Dewi (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The Keling Kumang Institute of Technology (ITKK) is dedicated to fulfilling the Tri Dharma of Higher Education, encompassing the domains of teaching, research, and community service. In the 2022/2023 academic year, the Entrepreneurship study program within the ITKK (Institute of Technology and Knowledge Creation) undertakes community service initiatives under the guidance of faculty members, aligning with the institution's overarching vision and goal. The primary objective of this service program is to enhance the knowledge of young individuals on the need of saving. To effectively promote financial literacy among young individuals, it is imperative that they possess adequate knowledge and skills in financial management. This is crucial as each person possesses varying capacities in addressing their respective needs. We engage in community service initiatives aimed at promoting awareness among young individuals regarding the significance of saving, accomplished through the process of socializing this concept. The introduction of effective financial management strategies is expected to encourage young individuals to allocate a portion of their income towards savings, thereby optimizing the utility of their funds. This practice aims to cultivate a sense of self-control and promote the practice of frugality in financial matters